Tolerance to the sedative and anxiolytic effects of diazepam is associated with different alterations of GABAA receptors in rat cerebral cortex - Ferreri, Maria Celeste (2015)
The clinical use of benzodiazepines is limited by the development of tolerance to their pharmacological effects. Tolerance to each of the pharmacological actions of benzodiazepines develops at different rates. The aim of this work was to investigate the mechanism of tolerance by performing behavioral tests in combination with biochemical studies. To this end, we administered prolonged treatments of diazepam to rats for 7 or 14days. Tolerance to the sedative effects of diazepam was detected by means of the open field test after the 7- and 14-day treatments, whereas tolerance to the anxiolytic actions of benzodiazepine manifested following only the 14-day treatment in the elevated plus maze. The cerebral cortical concentrations of diazepam did not decline after the diazepam treatments, indicating that tolerance was not due to alterations in pharmacokinetic factors. The uncoupling of GABA/benzodiazepine site interactions and an increase in the degree of phosphorylation of the GABAA receptor γ2 subunit at serine 327 in the cerebral cortex were produced by day 7 of diazepam treatment and persisted after 14days of exposure to benzodiazepine. Thus, these alterations could be part of the mechanism of tolerance to the sedative effects of diazepam. An increase in the percentage of α1-containing GABAA receptors in the cerebral cortex was observed following the 14-day treatment with diazepam but not the 7-day treatment, suggesting that tolerance to the anxiolytic effects is associated with a change in receptor subunit composition. The understanding of the molecular bases of tolerance could be important for the development of new drugs that maintain their efficacies over long-term treatments.